Integrasi ecosystem approach to aquaculture (EAA) dalam penilaian keberlanjutan multidimensi budidaya rumput laut di Teluk Sampolawa - Ma'ruf, Muhaimin Ali; Zairion, Zairion; Yulianto, Gatot; Mashar, Ali (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2026)
Seaweed cultivation is a major economic activity in Indonesia's coastal areas, but its sustainability challanged by complex socio-ecological interactions that are not fully captured by conventional sustainability assessment approaches. The Rapid Appraisal for Fisheries (Rapfish) method has been widely applied, but most studies still employ generic multidimensional attributes that do not explicitly reflect the principles of the Ecosystem Approach to Aquaculture (EAA). This study integrates EAA principles into the selection and grouping of Rapfish attributes to provide a holistic assessment of seaweed farming systems. This study aims to assess the multidimensional sustainability of Eucheuma cottonii cultivation in Sampolawa Bay, South Buton Regency. The analysis was conducted using the Multi-Dimensional Scaling (MDS) approach in the Rapfish tool across five sustainability dimensions: ecology, economy, society, technology, and institutions. The results showed that EAA integration enhances the comprehensive assessment framework, especially in the social and institutional dimensions. Overall, seaweed cultivation in Sampolawa Bay was categorized as moderately sustainable with an index value of 60.64. The social and ecological dimensions were the main pillars of sustainability, whereas the economic dimension was a limiting factor requiring attention. particularly regarding market accessibility and price stability to ensure the sustainability of seaweed cultivation in the future.